Hypothesis: Potentially Systemic Impacts of Elevated CO2 on the Human Proteome and Health - Duarte, Carlos M.; Jaremko, Łukasz; Jaremko, Mariusz (Frontiers in Public Health, 2020)
Uniform CO2 during human evolution (180 to 280 ppm) resulted, because of the role of the CO2-bicarbonate buffer in regulating pH, in rather constant pH (7.35 to 7.45) in human fluids, cells and tissues, determining, in turn, the narrow pH range for optimal functioning of the human proteome. Here we hypothesize that chronic exposure to elevated pCO2 with increasing atmospheric CO2 (>400 ppm) and extended time spent in confined, crowded indoor atmospheres (pCO2 up to 5,000 ppm) with urban lifestyles may be a major, largely overlooked, driver of changes in the performance of the human proteome. The reduced pH (downregulated from 0.1 to 0.4 units below the optimum pH) of extant humans chronically exposed to elevated CO2 is likely to lead to proteome malfunction due to protein misfolding, aggregation, charge distribution and altered interaction with other molecules (e.g. nucleic acids, metals, proteins, and drugs). Such alterations would have systemic effects helping explain the prevalence of syndromes (obesity, diabetes, respiratory diseases, osteoporosis, cancer, and neurological disorders) characteristic of the modern lifestyle. The risks chronic exposure to elevated CO2 poses to human health are too profound to be ignored and require testing with fit-for-purpose equipment and protocols along with indoor carbon capture technologies to bring CO2 levels to those (180 to 280 ppm) under which the humans proteome evolved.